ON THE ELECTROCATALYTIC PROPERTIES OF YCo₁₋ₓFeₓO₃(x = 0, 0.5 and 1) PEROVSKITE SERIES - ALEKSOVSKA, Slobotka; DIMITROVSKA-LAZOVA, Sandra; MIRČESKI, Valentin (Studia Universitatis Babeș-Bolyai Chemia, 2015)
The results on the investigation of the electrocatalytic activity of YCo1-xFexO3 (x = 0, 0.5 and 1) perovskites towards several redox reactions, are presented. The perovskites were synthesized by solution combustion method using citric acid as a fuel. They are isomorphous with orthorhombic perovskite structure, within the space group Pnma. The electrocatalytic properties of these perovskites were studied by cyclic voltammetry using paraffin impregnated graphite electrode (PIGE) modified with microcrystals of the investigated perovskites. Such modified electrodes were used to study their catalytic properties towards oxidation of OH- ions, oxidation of H2O2 in phosphate buffer and oxidation of CH3OH in alkaline solution. It was found that, in general, the catalytic activity is strongly dependent on the cobalt content.